2022
DOI: 10.1021/acsestengg.2c00212
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Phosphate Adsorption by Mg-Stirred Leaf Biochar in a Complex Water Matrix via Active MgO Facet Exposure

Abstract: In phosphate adsorption, the interaction between MgO and the carbon network in Mg-biochar is an overlooked factor that contributes to active MgO facet generation for enhancing phosphate adsorption. However, the complex water matrix adsorption mechanism underlying the adaptability of MgO-biochar and enhanced phosphate adsorption are not fully studied. Herein, Mg-stirred leaf biochar (Mg-SLBC) was prepared by the Mg-stirring modification method. Mg-SLBC possessed the highest adsorption capacity (79.28 mg g–1) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The performance tests in the real water matrices having different chemical compositions showed that the extent of kinetic retardation in 2,4-DBP degradation varied depending on water source (Figure c). Regardless of water matrix, Cu–Mg–C 3 N 4 /Fe­(VI) outperformed Cu–Mg–SiO 2 /Fe­(VI) and Cu–Mg–k10/Fe­(VI) in oxidative 2,4-DBP treatment and underwent marginal activity loss in Pearl River water and tap water (water quality parameters available in our previous study).…”
Section: Resultsmentioning
confidence: 99%
“…The performance tests in the real water matrices having different chemical compositions showed that the extent of kinetic retardation in 2,4-DBP degradation varied depending on water source (Figure c). Regardless of water matrix, Cu–Mg–C 3 N 4 /Fe­(VI) outperformed Cu–Mg–SiO 2 /Fe­(VI) and Cu–Mg–k10/Fe­(VI) in oxidative 2,4-DBP treatment and underwent marginal activity loss in Pearl River water and tap water (water quality parameters available in our previous study).…”
Section: Resultsmentioning
confidence: 99%
“…The pseudo‐first‐order and pseudo‐second‐order kinetic models were conducted to analyze the adsorption kinetic data (Figure S2). The higher correlation coefficient R 2 (R 2 >0.99) of the pseudo‐second‐order model (Table S1) illustrated the dominant function of chemisorption in the phosphate adsorption process [18] . Furthermore, to better verify the adsorption kinetics form of phosphate adsorption by 1.5Ce‐MOF, the Elovich model (Figure S3) and intraparticle diffusion model (Figure S4) were used to fit the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…The higher correlation coefficient R 2 (R 2 > 0.99) of the pseudo-second-order model (Table S1) illustrated the dominant function of chemisorption in the phosphate adsorption process. [18] Furthermore, to better verify the adsorption kinetics form of phosphate adsorption by 1.5Ce-MOF, the Elovich model (Figure S3) and intraparticle diffusion model (Figure S4) were used to fit the experimental data. The preferable fitting correlations of the two models (Table S2 and Table S3) also indicated the presence of chemisorption.…”
Section: Phosphate Adsorption On Ce-mofmentioning
confidence: 99%